Reliable Design of Electronic Equipment : An Engineering Guide - Natarajan, Dhanasekharan (Springer International Publishing : Imprint: Springer, 2015)
This book explains reliability techniques with examples from electronics design for the benefit of engineers. It presents the application of de-rating, FMEA, overstress analyses and reliability improvement tests for designing reliable electronic equipment. Adequate information is provided for designing computerized reliability database system to support the application of the techniques by designers. Pedantic terms and the associated mathematics of reliability engineering discipline are excluded for the benefit of comprehensiveness and practical applications. This book offers excellent support for electrical and electronics engineering students and professionals, bridging academic curriculum with industrial expectations.  .